Makna Sekapur Sirih pada Tarian Persembahan Andun dalam Upacara Pernikahan di Bengkulu Selatan - Anggi Mutiara; Utami Arsih (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The Andun Offering Dance is an important tradition in the traditional wedding ceremony of the Serawai people in South Bengkulu. It contains the main cultural symbol, Sekapur Sirih, which not only functions as a ritual complement but also has a philosophical meaning that represents the noble values ​​of the local community. This study aims to uncover the symbolic meaning of Sekapur Sirih in the Andun Offering Dance and explain the request to strengthen social relations between families united through the traditional wedding procession. The research method uses a qualitative descriptive approach through literature studies, observations, and interviews with traditional leaders of South Bengkulu. The results show that Sekapur Sirih contains values ​​of respect, welcome, purity, harmony, and prayer for the bride and groom. In addition, the existence of Sekapur Sirih functions as a cultural communication medium that maintains the identity of the Serawai people amidst social change. These findings preserve the importance of preserving traditional symbols in traditional ceremonies as an effort to maintain the continuity of local culture.